PERAN BOOK TAX DIFFERENCES MEMODERASI PENGARUH ARUS KAS AKRUAL DAN ARUS KAS OPERASI TERHADAP EARNINGS PERSISTENCE - Adhitya Putri Pratiwi; Lia Ira Sahara (Universitas Katolik Indonesia Atma Jaya, 2021)
This study aims to examine whether the book of tax difference moderates the effect of accrual cash flow and operating cash flow on earnings persistence. The contribution of this study is to explain and explore the previous research about the role of book tax difference on the effect of accrual cash flow, operating cash flow and earning persistence. This study uses samples of companies in the consumption sector that have profit during the 2014-2018 period. The samples are determined by using purposive sampling method with the number of samples that meet the criteria of 11 companies. Methods of analysis used are panel data regresion test and moderated regression analysis (MRA). Result of this study shows that accrual cash flow and operating cash flow had an impact on earnings persistence. While, book tax difference could not moderate the impact of accrual cash flow and operating cash flow on earnings persistence.